Analysis of the Effect of Mathematical Literacy Ability and Self-Concept of Students on Mathematical Communication Ability - Ahmad Fahrudin (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this research is to prove whether there is an impact between the variables of Mathematical Literacy and Self-Concept on Mathematical Communication. The research method used is experimental with correlation techniques. The research was conducted at the Economics Education Study Program, Faculty of Education and Social Sciences, Indraprasta University PGRI on students in semester 5 of the 2022/2023 academic year with a total sample of 35 students in class R5A. Based on the multiple correlation analysis, it was found that t count = 5.705 > t table = 3.06 for a significance level of 5% and regression analysis obtained Y = 7.546-0.016X1–0.017X2 this means that there is a significant and influential relationship between Mathematical Literacy, self-concept and Mathematical Communication